The Influence of Segmenting and Targeting on Consumer Satisfaction Through Purchasing Decisions as an Intervening Variable: Survey of Consumers of CIO Herbal, Syakira Herbal and Salma Herbal Tasikmalaya - Ricky Wahyudin; Kartawan Kartawan; Dedi Rudiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to determine and analyze the influence of segmenting and targeting on consumer satisfaction through purchasing decisions as an intervening survey variable for consumers of Cio Herbal, Syakira Herbal and Salma Herbal Tasikmalaya. The research method used is survey and quantitative methods. This research used a sample of 220 consumers of Cio Herbal, Syakira Herbal and Salma Herbal Tasikalaya. The sampling technique used was purposive sampling. Meanwhile, the data analysis technique uses Structural Equation Model (SEM) analysis. The results of the research show that there is an influence of Segmenting and Targeting on Consumer Satisfaction through Purchasing Decisions as an Intervening Variable in Consumers of Cio Herbal, Syakira Herbal and Salma Herbal Tasikmalaya both partially and simultaneously, meaning that the more focused segmenting and targeting is applied to CIO Herbal, Syakira Herbal and Salma Herbal Tasikmalaya, purchasing decisions will increase so that consumer satisfaction will also increase